Court Junks 1 of 2 graft cases against CHED exec - Nonato, Vince F. (Philippine Daily Inquirer, 2017)
The Sandiganbayan has dismissed one of the two graft charges filed against former Commission on Higher Education Executive Director Julito Vitriolo for his alleged involvement in the "diploma mill" operations of the state-run Pamantasan ng Lungsod ng Maynila (PLM).